Cotton-Tipped Plastic Swabs for SARS-CoV-2 RT-qPCR Diagnosis to Prevent Supply Shortages - Freire-Paspuel, Byron; Vega-Mariño, Patricio; Velez, Alberto; Castillo, Paulina; Gomez-Santos, Eliana Elizabeth; Cruz, Marilyn; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2020)
CDC and WHO guidelines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) diagnosis only recommend synthetic fiber swabs for nasopharyngeal (NP) sampling. We show that cotton tipped plastic swabs do not inhibit PCR and have equivalent performance to rayon swabs. Cotton tipped plastic swabs are massively produced worldwide and would prevent swabs supplies shortage during current high SARS-CoV2 testing demands, particularly on developing countries.